Semen and serum platinum levels in cisplatin‐treated survivors of germ cell cancer. (17th December 2021) - Malone, Eoghan R.; Lewin, Jeremy; Li, Xuan; Zhang, Wen‐Jiang; Lau, Susan; Jarvi, Keith; Hamilton, Robert J.; Hansen, Aaron R.; Chen, Eric X.; Bedard, Philippe L.
Abstract: Background: Testicular cancer survivors often have impaired gonadal function possibly related to chemotherapy. Platinum is a heavy metal that can be detected at low levels in serum many years after treatment, it is not known whether platinum also persists in semen and if platinum persistence in semen is associated with impaired fertility. Methods: Adult cisplatin‐treated testicular cancer survivors were enrolled. High‐Performance Liquid Chromatography‐tandem mass spectrometry was used to measure semen and serum platinum levels. Semen quality and DNA Fragmentation Index (DFI) were assessed. Results: From 11/2017 to 12/2019, 38 patients (median age 32 years; range: 19–52) were enrolled. Median cumulative cisplatin dose was 301 mg/m 2 (range: 274–404). Platinum levels were higher in semen than in blood ( p  = 0.03). Semen platinum levels were not significantly associated with time from last cisplatin dosing ( r  = −0.34; p  = 0.09) nor cumulative dose ( r  = −0.10, p  = 0.63). Sperm concentration was correlated with time from last cisplatin dosing ( r  = 0.58, p  < 0.001) but not with semen platinum level ( r  = −0.15, p  = 0.46). DFI was not significantly associated with time from last cisplatin dosing ( r  = 0.55, p  = 0.08) or semen platinum level ( r  = −0.32, p  = 0.33). In four patients with serial semen samples, platinum level decreased and sperm concentration and motility increased over time. Conclusions: Platinum is detected in semen of testicular cancer survivors at higher levels than matched blood samples. These preliminary findings may have important implications for the reproductive health of survivors of advanced testicular cancer, further study is needed to assess the relationship between platinum persistence in semen and recovery of fertility postchemotherapy. Abstract : Platinum is a heavy metal that can be detected at low levels in serum many years after treatment, it is not known that whether platinum also persists in semen and if platinum persistence in semen is associated with impaired fertility. Platinum is detected in semen of testicular cancer survivors at higher levels than matched blood samples. These preliminary findings may have important implications for the reproductive health of survivors of advanced testicular cancer, further study is needed to assess the relationship between platinum persistence in semen and recovery of fertility postchemotherapy.